Peran Kepemimpinan Dalam Meningkatkan Efektivitas Manajemen Pendidikan - Hayati, Ni’matul; Asrori, Mohammad; Jamilah, Jamilah (Universitas Pakuan, 2025)
THE ROLE OF LEADERSHIP IN IMPROVING THE EFFECTIVENESS OF EDUCATIONAL MANAGEMENTLeadership in education refers to the ability to influence, coordinate, and motivate individuals involved in the implementation and development of education, so that educational or school goals can be achieved effectively and efficiently. To achieve school goals effectively and efficiently, strong principal leadership is required. There are seven main characteristics of effective principal leadership, namely: (1) having a clear vision, (2) setting high expectations for achievement, (3) planning and providing positive and constructive feedback, (4) encouraging efficient use of time, (5) utilizing various learning resources, (6) integrating student development both individually and in groups, (7) conducting continuous assessment and improvement. It is clear that educational leadership plays a crucial role in educational management, because in essence every educational institution or agency needs a leader. This article reviews the definition of leadership, the function of educational leadership, the concept of leadership in schools, and principal leadership. According to Bachtiar Surin, as quoted by Maman Ukas, the term khalifah means a liaison or leader who is given the responsibility to convey or lead something.